Vegetative, endocrine and metabolic accompaniments of individual immune responses to adaptogenic balneotherapy - Oksana Mel'nyk; Zoryana Struk; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2019)
Background. Earlier in clinical observations four variants of the immune responses to adaptogenic balneotherapy at the Truskavets' spa have been identified. In 40,9% of patients, initially normal immune status did not change significantly; in 31,8%, the lower boundary level of immunity is completely normalized; in 22,7% moderate immunosuppression is reduced, but not up to normal; however, in 4,5% of people, initially normal level of immunity are transformed into moderate immunosuppression. All four variants of immune responses are virtually unmistakably predicted by a set of 20 predictors. The purpose of this study is to analyze vegetative, endocrine and metabolic accompaniments of individual immune responses to balneofactors of Truskavets' spa. Material and methods. The object of observation were 34 men and 10 women aged 24-70 years old, who came to the Truskavets' spa for the treatment of chronic pyelonephritis combined with cholecystitis in remission. The survey was conducted twice, before and after balneotherapy (drinking bioactive water Naftussya three times a day, ozokerite applications, mineral baths every other day for 7-10 days). Immune status evaluated on a set of I and II levels recommended by the WHO. The state of the autonomic nervous system is estimated by HRV ("CardioLab+HRV").